NUMERICAL MODELING OF LASER TRANSMISSION WELDING: STATE OF THE ART (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This work presents the current state of the numerical modeling of laser transmission welding. A review of publications with a similar theme was made and some aspects that remained outside the focus of the authors were highlighted. Laser transmission welding is a technological process, the physical description of which requires the consideration of several physical laws, which are discussed here. Works were reviewed in which the numerical model is based on: the law of conservation of energy, Fourier's law of heat transfer, Lambert-Beer's law of light propagation, Newton's law of convective heat transfer, Stefan-Boltzmann's law of radiant heat transfer, the Navier-Stokes equation for a fluid, the laws of mechanics for a deformable solid along with the criteria for plasticity. Since their joint solution in analytical form is not possible, the authors' approach is to single out one or several of the laws and use numerical methods to solve the differential equations that describe them. In this work, the use of several numerical methods is considered, and the finite element method is most often used for the discretization of space. The programs used by the authors for the numerical modeling of laser transmission welding are mentioned. The results obtained for the temperature field, heat affected zone and weld pool dimensions, voids, material degradation, residual stresses and weld pool flow rate are discussed. Particular attention is paid to the issues of calibration, verification and validation of numerical models. Some conclusions and directions are highlighted, emphasizing not so much the physical interpretation of the obtained results, but the essence of numerical modeling.